(untitled) (Pakistan Journal of Science, 2025)
Hydroponic (soilless culture) is an alternative flowers, fruits and vegetables production method. It may comprise pure water or substrate culture. Greenhouses are permanent structure that allow the farmers to grow vegetables and fruits year-round with mechanically-controlled temperature and irrigation system. Crop yield increases with ideal water and fertilizer use in hydroponic agriculture. Farmers are growing broccoli under greenhouse conditions using irrigation water with random nutrients application. However, database for optimum production of broccoli is required in order to reduce cost of production and increasing profit. Broccoli was grown on tap water, straight fertilizers and soluble fertilizer. The evaluation of these treatments (fertilizer concentration) was conducted on the basis of sulforaphane content, vitamin C, nitrate, weight of broccoli florets and total broccoli yield. Data collected from the experiment were statistically analyzed at 5% level of probability. Statical results shown that hydroponic recipe with soluble fertilizer shown better performance as compared to tap water and NPK straight fertilizer.